Investigation of Directly Print Pattern on Synthetic Leather Material - SEENI IBURAHIM, THAJUL MYDIN; KHIROTDIN, RD KHAIRILHIJRA (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This study aims to conduct research and investigate the direct printing of patterns on synthetic leather. Polyurethane leather (PU), polyvinyl chloride leather (PVC), and leather microfibre are all examples of synthetic leather. The main objective of the study is to determine the feasibility of the ink and printer head used to directly print patterns on the synthetic leather materials and to determine the suitable variation and optimum printing parameter to print patterns on synthetic leather material. However, some disadvantages were discovered, including an unpleasant odour and several health concerns induced by excessive UV radiation exposure. Thus, research is essential to discover and resolve such issues. Therefore, the full factorial design of the experiment method (DoE) was to be conducted by using the Minitab software that is mainly subjected to optimise and identify the significant parameter and level of factor to be used as the printing parameter to obtain the response parameter of line width and pattern edge. Furthermore, for the recommendation of the research, the simulation results can be improved by the application response surface method technique to refine the study and determine the crucial factors for the response variable.